Developing Islamic Religious Learning Media through Animated Video for Memorising Surah Al-A’la - Mega, Arianti; Hanawi, Ahmad Farid; Kaharuddin, Kaharuddin (South Sulawesi Education Development (SSED), 2026)
This study discusses the development of Islamic Religious Education learning media in the form of animated videos to help students memorize Surah Al-A’la. The purpose of this study is to describe the procedure for developing animation-based video learning media and to determine their validity and practicality. The research uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The results of the study show that the animated video media developed falls into the very valid category, as assessed by media experts (0.84) and material experts (0.92). The practicality test involving 27 grade VI students yielded a score of 85.02%. In contrast, Islamic Religious Education teachers scored 93.5%, indicating that this media is interesting, easy to use, and effective in supporting the learning process. Thus, this animated media is valid and practical for learning to memorize Surah Al-A’la in grade VI of elementary school.